2001
DOI: 10.1111/1467-9280.00326
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Implied Orientation Derived from Verbal Context on Picture Recognition

Abstract: Perceptual symbol systems assume an analogue relationship between a symbol and its referent, whereas amodal symbol systems assume an arbitrary relationship between a symbol and its referent. According to perceptual symbol theories, the complete representation of an object, called a simulation, should reflect physical characteristics of the object. Amodal theories, in contrast, do not make this prediction. We tested the hypothesis, derived from perceptual symbol theories, that people mentally represent the orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
420
4
11

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 600 publications
(506 citation statements)
references
References 23 publications
49
420
4
11
Order By: Relevance
“…The findings reported in this article add to the growing body of evidence that language comprehension routinely involves the activation of perceptual representations (Pecher, Zeelenberg, & Barsalou, 2003;Richardson et al, 2003;Stanfield & Zwaan, 2001;Zwaan et al, 2002;Zwaan & Yaxley, 2003a, 2003b. However, the current findings constitute an advance over this earlier research in several ways.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The findings reported in this article add to the growing body of evidence that language comprehension routinely involves the activation of perceptual representations (Pecher, Zeelenberg, & Barsalou, 2003;Richardson et al, 2003;Stanfield & Zwaan, 2001;Zwaan et al, 2002;Zwaan & Yaxley, 2003a, 2003b. However, the current findings constitute an advance over this earlier research in several ways.…”
Section: Resultssupporting
confidence: 58%
“…We assume that dynamic mental representations are perceptual traces that are stored as temporal patterns of activation that unfold over time corresponding to a certain perceptual experience. Extending the logic behind the Stanfield and Zwaan (2001) and the Zwaan et al (2002) experiments, we predicted that comprehension of a sentence describing a motion event should facilitate the perception of an analogous visual motion event relative to a mismatching motion event. We tested this idea using sentences such as (1) and (2).…”
Section: The Present Studymentioning
confidence: 97%
See 1 more Smart Citation
“…Zwaan, Stanfield, and Yaxley (2002), for example, found that after reading a sentence such as The ranger saw the eagle in the sky participants were faster to judge a picture of an eagle as mentioned versus not mentioned in the sentence when the depicted shape (wings outstretched) matched the shape implied in the sentence (the eagle is in the sky) compared to when it did not match (perched). Stanfield and Zwaan (2001) observed related findings concerning object orientation, while Yaxley and Zwaan (2005) provided evidence that readers simulate even the visibility of described scenes (e.g., as foggy versus clear). The above observations have generally been taken as support for the seamless interaction of visual and linguistic representations (Tanenhaus et al, 1995), on the one hand, and for multi-modal sensorimotor-derived meaning representations on the other (Barsalou, 1999b).…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, this last set of studies revealed that words associated with vertical or horizontal space were not enough to lead to interference effects, but that the results were caused by mental imagery. Importantly, building a mental simulation can also facilitate the processing of visually congruent information (Glenberg & Kaschak, 2002;Kaschak et al, 2005;Stanfield & Zwaan, 2001;Zwaan, Stanfield, & Yaxley, 2002). The critical difference between interference and facilitation seems to be the length of time between the presentation of the linguistic stimulus and the perceptual stimulus.…”
Section: Grounding Concrete Conceptsmentioning
confidence: 99%